Strategi Koping Maladaptif Lansia Jepang: Tindakan Kriminalitas sebagai Upaya Bertahan di Tengah Keterbatasan - Linda Febriyani; Dewi Saraswati Sakariah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
The increasing elderly population in Japan has contributed to a significant rise in elderly criminality in recent years. This study aims to analyze how criminal behavior functions as a coping mechanism among elderly Japanese, particularly those affected by poverty and loneliness. A literature study and descriptive analysis were employed using data from various sources such as TBS News, CNN World, FBS Fukuoka News, previous research, scientific articles, books, and other relevant references. Data were processed qualitatively using categorization techniques, including open, axial, and selective coding. The findings reveal that criminal acts committed by the elderly reflect a dominance of emotion-focused coping strategies, namely, escape-avoidance, emotional distancing, and a combination of both. Elderly individuals facing economic hardships, such as the loss of income post-retirement or imbalances between income and living costs, tend to commit minor crimes to be incarcerated and meet their basic needs. Meanwhile, those experiencing psychological distress such as loneliness, social isolation, and lack of familial affection often choose imprisonment as a means of withdrawing from a distressing reality. A combination of avoidance and emotional distancing was found among elderly individuals facing both economic and psychological pressures. Prison is perceived as a safe space that offers basic facilities and social interaction, thereby contributing to the phenomenon of repeat offenses or recidivism among the elderly. In conclusion, criminal behavior among elderly Japanese can be understood as a maladaptive coping strategy emerging in response to an inability to positively cope with life’s limitations.